Pediatric non–Down’s syndrome acute megakaryoblastic leukemia patients in China: A single center's real-world analysis - Zhang, Aoli; Liu, Lipeng; Zong, Suyu; Chen, Xiaoyan; Liu, Chao; Chang, Lixian; Chen, Xiaojuan; Yang, Wenyu; Guo, Ye; Zhang, Li; Zou, Yao; Chen, Yumei; et al. (Frontiers in Oncology, 2022)
Non-Down’s syndrome acute megakaryocytic leukemia (non-DS-AMKL) is a subtype of childhood acute myeloid leukemia (AML), whose prognosis, prognostic factors and treatment recommendations have not yet to be defined in children. We conducted a retrospective study with 65 children with newly diagnosed non-DS-AML from August 2003 to June 2020 to investigate the clinical impact of factors and clinical outcome. Among all 65 patients, 47 of them were treated at our center who received three different regimens due to time point of admission (CAMS-another, CAMS-2009 and CAMS-2016 protocol), and the efficacy were compared. Patients with newly diagnosed non-DS-AMKL accounted for 7.4% of pediatric AML cases. The median age of the patients was 18 months at diagnosis, and over 90% of them were under three-years-old. The overall survival (OS) rates were 33.3%±1.7%, 66.7%±24.4% and 74.2%±4.0% for three groups (CAMS-another, CAMS-2009 and CAMS-2016 regimen), respectively. In CAMS-2016 group, the complete remission (CR) rate after induction was 67.7 % (21/31), while the total CR rate after all phases of chemotherapy was 80.6% (25/31). The 2-year survival probability did not significantly improve in patients underwent HSCT when compared with non-HSCT group (75.0%±4.7% vs. 73.9%±4.6%, p=0.680). Those who had a "dry tap" during BM aspiration at admission had significantly worse OS than those without "dry tap" (33.3%±8.6% vs. 84.0%±3.6%, p=0.006). Moreover, the results also revealed that patients with CD34+ had significantly lower OS (50.0%±6.7% vs. 89.5%±3.5%, p=0.021), whereas patients with CD36+ had significantly higher OS than those who were negative (85.0%±4.0% vs. 54.5%±6.6%, p=0.048). In conclusion, intensive chemotherapy resulted in improved prognosis of non-DS-AMKL children and subclassification may base on “dry tap” and immunophenotypic. Although some progress has been made, outcomes of non-DS-AMKL children remain unsatisfactory, especially in HSCT group, when compared with other AML types.